Immune modulation of liver sinusoidal endothelial cells by melittin nanoparticles suppresses liver metastasis - Xiang Yu (Nature Portfolio, 2019)
Liver sinusoidal endothelial cells are known to promote immune tolerance in liver. Here, the authors target these cells using melittin nanoparticles and show alterations in the liver immune environment and suppression of liver metastases.